Calculate: (x-5)/(3)+(3x-1)/(2)=4

Expression: $\frac{ x-5 }{ 3 }+\frac{ 3x-1 }{ 2 }=4$

Multiply both sides of the equation by $6$

$2\left( x-5 \right)+3\left( 3x-1 \right)=24$

Distribute $2$ through the parentheses

$2x-10+3\left( 3x-1 \right)=24$

Distribute $3$ through the parentheses

$2x-10+9x-3=24$

Collect like terms

$11x-10-3=24$

Calculate the difference

$11x-13=24$

Move the constant to the right-hand side and change its sign

$11x=24+13$

Add the numbers

$11x=37$

Divide both sides of the equation by $11$

$\begin{align*}&x=\frac{ 37 }{ 11 } \\&\begin{array} { l }x=3 \frac{ 4 }{ 11 },& x=3.\overset{ \cdot }{ 3 } \overset{ \cdot }{ 6 } \end{array}\end{align*}$